Thinking Strategically about Revenue Administration Reform : The Creation of Integrated, Autonomous Revenue Bodies - Junquera-Varela, Raul Felix (World Bank, Washington, DC, 2019)
Over the past two decades, two trends in tax administration reform have emerged – granting increased autonomy to tax administrations and establishing a unified integrated revenue authority (IRA) charged with administering both tax and customs laws and, in some cases, social security. This paper reviews the theory and practice of these revenue administration models and synthesizes lessons learned from the World Bank’s engagement with clients in recent years. The paper looks at several case studies across the world on the reform design as well as results of integration or increased autonomy. Semi-autonomous and integrated revenue administration models have the potential to bring crucial improvements to the efficiency and effectiveness of tax administration. The implementation shows both successes and challenges. The paper concludes with listing pre-conditions for these reforms including need for comprehensive approach of combining increased autonomy with improved administration processes and anticorruption efforts; importance of building collation of all revenue bodies prior to integration; and focus on non-revenue collecting functions of customs administration.